Luther and Cromwell - Headley, Joel Tyler (J.S. Taylor; [etc., etc.], 1850)
Luther.--Letters and speeches of Oliver Cromwell.--Thier's revolution.--Alison's History of Europe.--The one progressive principle.--The apostles Paul and John.